Development and Initial Validation of the Caregiver Perceptions About Communication With Clinical Team Members (CAPACITY) Measure. (December 2019) - Van Houtven, Courtney Harold; Miller, Katherine E. M.; O'Brien, Emily C.; Wolff, Jennifer L.; Lindquist, Jennifer; Kabat, Margaret; Campbell-Kotler, Margaret; Henius, Jennifer; Voils, Corrine I.
Despite the important role that family caregivers play managing the care of persons with complex health needs, little is known about how caregivers perceive themselves to be recognized and valued by health care professionals. Our objective was to develop and validate a novel measure, the CA regiver P erceptions A bout C ommun I cation with Clinical T eam members (CAPACITY) instrument. Questions focus on perceived quality of communication with the health care team and the extent to which caregivers believe that the health care team considers their capacity and preferences in decision making. A confirmatory factor analysis supported a two-factor solution addressing communication and capacity. Internal consistency reliability was .90 for the communication domain and .93 for the capacity domain. Correlations between these two subscales and individual difference measures provided evidence of convergent and discriminant validity. The CAPACITY instrument may be a useful performance measure that quantifies the extent to which caregivers' experience person- and family-centered health care.